The impact of an ECV service is limited by antenatal breech detection: a retrospective cohort study - Hemelaar, J; Lim, L; Impey, L (Wiley, 2015)
External cephalic version (ECV) reduces the chance of breech presentation at term birth and lowers the chance of a cesarean delivery. ECV services are now in place in many units in the United Kingdom but their effectiveness is unknown. The aim of this study was to investigate the reasons for breech presentation at term birth.We performed a retrospective cohort study of 394 consecutive babies who were in breech presentation at term birth in a large United Kingdom maternity unit that offers ECV. The cohort was analyzed over two time periods 10 years apart: 1998-1999 and 2008-2009.Only 33.8 percent of women had undergone a (failed) ECV attempt. This low proportion was mainly because breech presentation was not diagnosed antenatally (27.9%). Other contributing factors were: ECV not offered by clinicians (12.2%), ECV declined by women (14%), and contraindications to ECV (10.7%). Over the 10-year period, the proportion of breech presentations that were not diagnosed antenatally increased from 23.2 to 32.5 percent (p = 0.04), which constituted 52.8 percent of women who had not undergone an ECV attempt in 2008-2009. Failure of clinicians to offer ECV reduced from 21.6 to 3.0 percent (p = 0.0001) and the proportion of women declining ECV decreased from 19.1 to 9.0 percent (p = 0.005). Overall, ECV attempts increased from 28.9 to 38.5 percent (p = 0.05).Although ECV counseling, referral, and attempt rates have increased, failure to detect breech presentation antenatally is the principal barrier to successful ECV. Improved breech detection would have a greater impact than methods to increase ECV success rates.